The Neuroprotective Effects of Ginsenoside Rd Pretreatment in a Rat Model of Spinal Cord Ischemia-Reperfusion Injury - Kim,Dong Jung (2022)
ABSTRACT Introduction: Paraplegia may develop as a result of spinal cord ischemia-reperfusion injury in patients who underwent thoracoabdominal aortic surgery. The objective of this research is to determine the neuroprotective effects of ginsenoside Rd pretreatment in a rat model of spinal cord ischemia-reperfusion injury. Methods: Sprague-Dawley rats (n=36) were randomly assigned to three groups. The sham (n=12) and control (n=12) groups received normal saline orally. The Rd group (n=12) received ginsenoside Rd (100 mg/kg) orally 48 hours before the induction of spinal cord ischemia. Spinal cord ischemia was induced by aortic occlusion using a Fogarty balloon catheter in the Rd and control groups. A neurological assessment according to the motor deficit index and a histological evaluation of the spinal cord were performed. To evaluate the antioxidant activity of ginsenoside Rd, malondialdehyde levels and superoxide dismutase activity were determined. Further, the tissue levels of tumor necrosis factor-alpha and interleukin-1 beta were measured. Results: The Rd group showed significantly lower motor deficit index scores than did the control group throughout the entire experimental period (P<0.001). The Rd group demonstrated significantly greater numbers of normal motor neurons than did the control group (P=0.039). The Rd group exhibited decreased malondialdehyde levels (P<0.001) and increased superoxide dismutase activity (P=0.029) compared to the control group. Tumor necrosis factor-alpha and interleukin-1 beta tissue levels were significantly decreased in the Rd group (P<0.001). Conclusion: Ginsenoside Rd pretreatment may be a promising treatment to prevent ischemia-reperfusion injury in patients who undergo thoracoabdominal aortic surgery.